Non‐family support for breastfeeding maintenance among career women in Taiwan: A qualitative study. Issue 3 (15th August 2013) - Chang, Shu‐min; Rowe, Jennifer; Goopy, Suzanne
<x xml:space="preserve">Abstract</x> The purpose of the study was to describe the influence of non‐family‐based support on breastfeeding practices among career women in Taiwan during the first four postnatal months. A qualitative, case study approach was used to investigate the phenomenon. A purposive sample of 14 women was recruited and took part in two to three in‐depth interviews. The data were transcribed and analysed using descriptive content analysis. It was found that non‐family supports had significant influence on their efforts to maintain breastfeeding. Women faced a number of challenges to breastfeeding. The services provided by in‐centre care organizations, the resources and organizations accessed through the Internet, and the support provided by colleagues in their workplaces supported women's efforts to maintain breastfeeding. Given the low breastfeeding maintenance rates in Taiwan and the changing societal structure where fewer families rely on family support, the findings highlight the resources, programmes and nursing practice which might support women's needs and promote breastfeeding among career women.